2020
DOI: 10.1111/cns.13443
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation analysis with methylation‐sensitive high‐resolution melting (MS‐HRM) reveals gene panel for glioma characteristics

Abstract: Introduction Local DNA hypermethylation is a potential source of cancer biomarkers. While the evaluation of single gene methylation has limited value, their selected panel may provide better information. Aims This study aimed to analyze the promoter methylation level in a 7‐gene panel in brain tumors and verifies the usefulness of methylation‐sensitive high‐resolution melting (MS‐HRM) for this purpose. Methods Forty‐six glioma samples and one non‐neoplastic brain sample were analyzed by MS‐HRM in terms of SFRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…Epigenetic modification of DNA methylation has been reported in a large number of studies on glioma. Numerous cell cycle control genes, DNA damage repair genes, and tumor invasionrelated genes are methylated in their promoter regions, which leads to changes in the biological functions of glioma cells (19)(20)(21). Studies have shown that the IDH1/2 mutations is closely associated with DNA methylation in gliomas genomes (22).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic modification of DNA methylation has been reported in a large number of studies on glioma. Numerous cell cycle control genes, DNA damage repair genes, and tumor invasionrelated genes are methylated in their promoter regions, which leads to changes in the biological functions of glioma cells (19)(20)(21). Studies have shown that the IDH1/2 mutations is closely associated with DNA methylation in gliomas genomes (22).…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest in this context are sex-bound disparities in the epigenetic regulation of glioma, and how they impact downstream gene expression. There is accumulating evidence that gliomas display sex-specific methylation patterns [ 10 , 11 ]. MGMT promoter methylation is more commonly found in females with GBM, with a subsequent better outcome after treatment with alkylating agent temozolomide (TMZ) [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This approach is semiquantitative if an unknown sample is compared with standards of known methylated vs unmethylated ratio [ 57 ]. Overall, MS-HRM offers a fast and relatively cost-effective estimation of methylation rate [ 50 ] and has a great use in the analysis of clinical samples [ 58 ].…”
Section: Standard Methods Of Analysismentioning
confidence: 99%